Synthetic detergents: 100 years of history - Kogawa, Ana Carolina [UNESP]; Cernic, Beatriz Gamberini [UNESP]; do Couto, Leandro Giovanni Domingos [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Springer Nature, 2017)
In the year 2016 the synthetic detergents complete 100 years and in this story they evolved as cleaners. They are already part of the routine of thousands of people worldwide. For a higher power of cleaning of the detergent, today, are added phosphates, the main responsible for environmental problems. After 100 years of synthetic detergents, the effect of the combination of various cleaners on the environment is a gap. Legislation and guidelines about the other components of the formula of cleaners still missing. Even the term biodegradable can be best placed on the diversity of products currently entitled biodegradable. A lot attitudes can still be taken to continuously improve the relationship between the parties involved, animals, plants, waters and men, so that in another 100 years continues to exist this interaction with the environment without destroying it. The marketing used by synthetic detergent companies evolved a lot over the years and showed maturity to deal with changes in theories and strategies for promotion and even with the constant social reform that its consumer lived, accompanying them intelligently to be able to capture their changing needs and desires, and so assemble the best way to connect to them. This paper focuses on the subject synthetic detergents as well as (i) types and applications, (ii) threats, (iii) sustainability, (iv) legislation, (v) packaging and (vi) marketing strategies.
Keywords: Biodegradable; Environment; Marketing; Phosphates; Synthetic detergents